Manipulation of Vote Choice – Impediment to the Electoral Integrity in Turkey? - Szymański, Adam; Wódka, Jakub (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2017)
Turkey has had a fairly long tradition of regular, competitive polls and multi-party democracy begun in 1946. However, in the last decade, with the consolidation of Justice and Development Party’s (AKP, Adalet ve Kalkınma Partisi) grip on power, there has been a growing concern about the integrity of elections in this state. In subsequent elections the ruling party resorted to a plethora of means inhibiting their competitiveness. Thus, the article seeks to survey the extent of election malpractices in Turkey with the focus on manipulation of vote choice as most disturbing group of electoral malpractices and, without prejudging, to address the fundamental questions about whether elections in Turkey, notwithstanding the irregularities, still meet democratic, international standards, or whether Turkey is sliding into electoral autocracy.

Od 1946 r., Turcja jest demokracją wielopartyjną – w państwie tym regularnie odbywają się wolne, konkurencyjne wybory. Jednak w ostatnim dziesięcioleciu, wraz z konsolidacją władzy przez Partię Sprawiedliwości i Rozwoju, pojawia się coraz więcej wątpliwości co do uczciwości wyborów. Partia rządząca zaczęła uciekać się do szeregu środków, ograniczających ich konkurencyjność. Celem artykułu jest ukazanie skali nadużyć wyborczych w Turcji, z naciskiem na jeden z trzech głównych obszarów manipulacji wyborczych, to jest manipulowanie “preferencjami wyborców” (vote choice), który wydaje się być najbardziej problematyczny. Ambicją autorów jest udzielenie odpowiedzi na pytanie, czy wybory w Turcji, mimo obserwowanych nieprawidłowości, nadal spełniają międzynarodowe standardy, czy też Turcja staje się ‘wyborczą autokracją’?
Manipulowanie preferencjami wyborczymi – czynnik ograniczający uczciwość wyborów w Turcji?
Keywords: elections; wybory; electoral malpractice; nieprawidłowość wyborcza; democratisation; demokratyzacja; Turkey; Turcja; Justice and Development Party; Partia Sprawiedliwości i Rozwoju